Hubungan Status Gizi dan Stres dengan kejadian Amenorea Sekunder - Desi Pramita Sari; Trisna Yuni Handayani; Elly Sustiyani (STIKes Payung Negeri Pekanbaru, 2021)
Secondary amenorrhea is the absence of menstruation for three cycles or 6 cycles after previously getting a regular menstrual cycle. The incidence is about 1-5% in women of reproductive age This study aims to determine the relationship between nutritional status and stress with the incidence of secondary amenorrhea in adolescents. This study is a quantitative analytic study with a cross sectional design, the sample in this study was midwifery students experiencing secondary amenorrhea at the Mitra Bunda Health Institute, totaling 43 respondents. Collecting data in this study in the form of a questionnaire. The analysis used in this study was chi square. The results showed that there was a relationship between nutritional status and secondary amenorrhea, P value 0.004 (< 0.05). There is a relationship between stress and secondary amenorrhea P value 0.008 (< 0.05). The conclusion in this study is that adolescents should always maintain their body's nutritional intake and manage stress properly because it will affect body functions related to the reproductive system, this is intended to avoid menstrual disorders which result in various other complications related to the reproductive system.